STUDI KOMPERATIF SISTEM GADAI KONVENSIONAL DENGAN GADAI SYARIAH DI INDONESIA - Aprilianti, Aprilianti (Lampung University)
Pawn broking services in Indonesia, in addition to impose a conventional mortgage system set out in PP 103 2000 On Pawnshop, also impose sharia pawning system based on the provisions of Islamic law which is based on the Quran. In the conventional mortgage loan bears an interest rate that is accumulative and double for its services, while at the syariah pawn does not bear interest. Customer charged deposit money services, maintenance, preservation and biay assessment specified in the initial agreement.Â Keywords: Conventional Pawn, Pawn sharia